2012
DOI: 10.1001/archdermatol.2012.2894
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Tattoos With a Picosecond Alexandrite Laser

Abstract: To study a picosecond 755-nm alexandrite laser for the removal of tattoos to confirm the efficacy of this therapy, focusing on the effect of therapy on the target lesion as well as the surrounding tissues and quantifying the number of necessary treatments. Design: Fifteen patients with tattoos were enrolled. Treatments were scheduled approximately 6Ϯ2 weeks apart. Standard photographs using 2-dimensional imaging were taken at baseline, before each treatment, and 1 month and 3 months after the last treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
2
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 10 publications
2
98
2
5
Order By: Relevance
“…[10][11][12][13][14][15] In the present study, we also found that asphalt-and sand-embedded tattoos caused by abrasions from a fall or motor-vehicle accident and a graphite-embedded, pencil point puncture tattoo were effectively and safely cleared after 1-3 sessions of 1,064-nm, picosecond-domain Nd:YAG laser treatment. We suggest that the explosive but selective delivery of photoacoustic waves could have contributed to the rapid clinical improvement in the traumatic tattoos from various foreign bodies.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…[10][11][12][13][14][15] In the present study, we also found that asphalt-and sand-embedded tattoos caused by abrasions from a fall or motor-vehicle accident and a graphite-embedded, pencil point puncture tattoo were effectively and safely cleared after 1-3 sessions of 1,064-nm, picosecond-domain Nd:YAG laser treatment. We suggest that the explosive but selective delivery of photoacoustic waves could have contributed to the rapid clinical improvement in the traumatic tattoos from various foreign bodies.…”
supporting
confidence: 77%
“…9 Furthermore, successive in vivo and in vitro experiments have found picosecond-domain lasers to be more advantageous in breaking down tattoo pigments of various colors and constituents than nanosecond-domain lasers. [10][11][12][13][14][15] In the present case series study, we analyzed the clinical efficacy and safety of a picosecond-domain Nd:YAG laser in the treatment of traumatic tattoos of various causes.…”
Section: Introductionmentioning
confidence: 99%
“…The logic is that ns pulse duration might be too long for effective photothermolysis of small tattoo particles having thermal relaxation time (TRT) in ps ranges. These ps pulse lasers have shown better performance than ns lasers in either tattoo clearance per treatment session or the pain level in both preclinical studies [6] and clinical studies [7,8]. Currently tattoo laser treatments are usually performed in multiple sessions with several weeks apart [9].…”
Section: Introductionmentioning
confidence: 99%
“…They may lead to fewer adverse effects because they confine energy to their target, and lower fluences are required. [79][80][81] Fractionated picosecond handpieces have been developed for resurfacing and rejuvenation, including the 755-nm picosecond alexandrite laser PicoSure (Cynosure, Westford, MA), which contains a diffractive lens array (DLA) and the dual-wavelength 532/1064-nm holographic fractionated picosecond laser, PicoWay Resolve (Syneron Candela, Irvine, CA). The PicoSure with DLA received US Food and Drug Administration (FDA) approval in 2014 to treat acne scarring and rhytides, 81 while the PicoWay received FDA approval in 2014 to treat all tattoo colors.…”
Section: Picosecond Lasersmentioning
confidence: 99%